2014
DOI: 10.1097/mnm.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of 18F-FDG PET/CT in therapeutic decision-making of potentially curable esophageal adenocarcinoma

Abstract: In patients who are considered to be potentially curable after conventional imaging, F-FDG PET/CT can detect unsuspected sites of distant metastases (M1b) in a significant number of cases and thus contribute to the clinical decision-making process. PET/CT should be an integral part of the staging workup of patients with esophageal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…CT imaging is utilized for detecting distant metastasis, and PET scanning may detect distant disease-altering management [18, 19] in approximately 15–20 % of patients otherwise considered to have localized disease (on CT) and thereby alter patient management, i.e., upstaging. As precise assessment of local disease extent is not important if metastasis is identified, it may be most efficient to obtain a CT scan or PET scan prior to EUS and FNA.…”
Section: Clinical Staging Is Now Used To Guide Therapymentioning
confidence: 99%
“…CT imaging is utilized for detecting distant metastasis, and PET scanning may detect distant disease-altering management [18, 19] in approximately 15–20 % of patients otherwise considered to have localized disease (on CT) and thereby alter patient management, i.e., upstaging. As precise assessment of local disease extent is not important if metastasis is identified, it may be most efficient to obtain a CT scan or PET scan prior to EUS and FNA.…”
Section: Clinical Staging Is Now Used To Guide Therapymentioning
confidence: 99%
“…The basis for this proposal is the low rate at which PET identifies occult metastatic disease above and beyond physical examination and CT. However, there is no universally accepted threshold for what constitutes "a low rate" leading to the converse and prevailing conclusion that PET should be used routinely (10,16). From a patient's perspective, even a 5% chance to avoid ineffective curative-intent treatments for stage IV disease would seem to be of great value.…”
Section: Discussionmentioning
confidence: 99%
“…Also not in context with radiotherapy treatment planning FDG-PET has proven to be successful in finding of distant metastasis in patients with oesophageal carcinoma. Purandare et al found in 25 of 156 patients with oesophageal carcinoma previously unknown distant metastasis leading to an upstaging to stage IV [47]. However in local lymph node staging FDG-PET/CT is discussed controversially [48] and further studies need to be performed, especially in the context with radiation treatment.…”
Section: Discussionmentioning
confidence: 99%